Inovasi dan Strategi Pemasaran UMKM Bakso untuk Meningkatkan Pendapatan - Siregar, Sri Intan Nur’aini; Dalimunthe , Siti Nurkholijah; Putri , Naila Atika; Siregar, Nadya Faiza; Zainarti, Zainarti (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
This research is motivated by the increasingly fierce competition in the culinary MSME sector, especially in meatball businesses, which require business actors to develop innovative and adaptive marketing strategies to maintain competitiveness and increase revenue. The objectives of this study are to analyze the forms of product innovation undertaken by meatball MSMEs, digital marketing strategies that leverage online platforms to expand consumer reach, conventional marketing strategies that remain relevant for building closeness with local customers, and to examine how integrating both approaches contributes to increased revenue. This study uses a descriptive qualitative method; data are collected through a literature review, then analyzed using data reduction techniques, data presentation, and systematic conclusion drawing. The results show that product innovation, such as menu variations, improved raw material quality, and flavor differentiation, are proven to expand market segments and increase perceived value in the eyes of consumers, while digital marketing strategies through the use of social media, digital catalogs, and interactive promotions significantly increase brand visibility and accelerate the purchasing process; at the same time, conventional marketing strategies continue to play a vital role in building trust through direct interaction, friendly service, and local promotions, so that both work complementary in forming a marketing ecosystem that strengthens loyalty and improves the revenue performance of meatball MSMEs. These findings have theoretical implications for the importance of integrating innovation and marketing as a unified business strategy, and offer practical implications for culinary MSMEs to optimize product creativity and utilize marketing channels in an integrated manner.